Effect of Ultrasound in the enhancement of Protein Metabolism and Enzyme Activities in the Fat body of Fifth Instar Silkworm, Bombyx mori L. - P. Naga Jyothi (Research Aspects in Biological Science Vol. 7, 2022)
Under the influence of ultrasound, protein metabolism parameters such as total, soluble proteins, free amino acids, and activity levels of protease, glutamate dehydrogenase, aspartate amino transferase, and alanine aminotransferase were measured in the fat body of the fifth instar larva of the silkworm, Bombyx mori. On these parameters, ultrasonography generally has an elevating effect. The events of histogenesis and histolysis connected to the metamorphosis of the silkworm are correlated with changes in the levels of certain biochemical components. Under the impact of ultrasound, the metabolism of proteins is accelerated, resulting in increased spinning activity, increased protein turnover in silk, and increased sericultural production. Enhancement of proteins by ultrasound clearly documented the induction of severe proteolysis and transamination of amino acids.